-6(-5y+7)-8y=6(y-8)-8

Simple and best practice solution for -6(-5y+7)-8y=6(y-8)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(-5y+7)-8y=6(y-8)-8 equation:


Simplifying
-6(-5y + 7) + -8y = 6(y + -8) + -8

Reorder the terms:
-6(7 + -5y) + -8y = 6(y + -8) + -8
(7 * -6 + -5y * -6) + -8y = 6(y + -8) + -8
(-42 + 30y) + -8y = 6(y + -8) + -8

Combine like terms: 30y + -8y = 22y
-42 + 22y = 6(y + -8) + -8

Reorder the terms:
-42 + 22y = 6(-8 + y) + -8
-42 + 22y = (-8 * 6 + y * 6) + -8
-42 + 22y = (-48 + 6y) + -8

Reorder the terms:
-42 + 22y = -48 + -8 + 6y

Combine like terms: -48 + -8 = -56
-42 + 22y = -56 + 6y

Solving
-42 + 22y = -56 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
-42 + 22y + -6y = -56 + 6y + -6y

Combine like terms: 22y + -6y = 16y
-42 + 16y = -56 + 6y + -6y

Combine like terms: 6y + -6y = 0
-42 + 16y = -56 + 0
-42 + 16y = -56

Add '42' to each side of the equation.
-42 + 42 + 16y = -56 + 42

Combine like terms: -42 + 42 = 0
0 + 16y = -56 + 42
16y = -56 + 42

Combine like terms: -56 + 42 = -14
16y = -14

Divide each side by '16'.
y = -0.875

Simplifying
y = -0.875

See similar equations:

| 6y^2-20y+16=o | | 2.5x+2.4=2.3 | | 5(7+2b)=25 | | A=1/2-b^2 | | 41412=1.19x | | 2(a+2)=6(a-2) | | 4h-2h-h+2=11 | | -4a-a=-5 | | 10/20=n/4 | | (3x+6)+(1x+2)=4(1x-1)+8 | | -3h+2=8 | | 17j-17j+j=16 | | 3p+2-1=-2 | | -6u-26=2(u-5) | | X-5=w | | -4q-(-18q)=-14 | | 4b+4b-7=25 | | 6a-1=2 | | 12=3(7-2) | | 2x-2x+2x+4x-5x=4 | | 4x+.5(8x-6)=2(4x+3) | | 0=12b-12 | | -5j+-16j+13j=16 | | 12=3(-2-2) | | h^2+b^2=8.5-h^2 | | x^2+y^2=8.5-h^2 | | 2c-(-6)=12 | | 5x-1+1x+15=6+5x+14-2x | | b+9=8+7 | | -6x-6(-3x)=-24 | | 2y+11=6-y | | (3k+1)x^2+2x=1 |

Equations solver categories